2020
DOI: 10.1007/s12253-020-00854-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Microparticles, Thrombin-antithrombin and VEGF Levels in Colorectal Cancer Patients Undergoing Chemotherapy

Abstract: Hypercoagulable state and neoangiogenesis are common phenomena associated with malignancy. Cancer patients have increased levels of circulating endothelium-derived microparticles (EMPs), which have been hypothesized to be involved in numerous pathophysiological processes. Hemostasis and angiogenesis are also activated in colorectal cancer (CRC) patients. The study aimed to investigate potential influence of chemotherapy on EMPs, thrombin anti-thrombin complex (TAT) and vascular endothelial growth factor (VEGF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Angiogenesis, the process of formation of new blood vessels, is fundamental for the growth of all tumor cells, including CRC [ 129 ]. VEGF is a member of the platelet-derived growth factor family that includes related glycoproteins, such as VEGF-A, VEGF-B, VEGF-C, and VEGF-D [ 130 ].…”
Section: Crc Pathogenesismentioning
confidence: 99%
“…Angiogenesis, the process of formation of new blood vessels, is fundamental for the growth of all tumor cells, including CRC [ 129 ]. VEGF is a member of the platelet-derived growth factor family that includes related glycoproteins, such as VEGF-A, VEGF-B, VEGF-C, and VEGF-D [ 130 ].…”
Section: Crc Pathogenesismentioning
confidence: 99%
“…The published by Martini et al [ 41 ] showed that quantitative analysis of the VEGF-121 isoform, which is mainly detected in circulating blood, might be a predictor of response to anti-angiogenetic treatment. Interestingly, in recent a publication, it has been presented that in patients with colorectal cancer who underwent chemotherapy VEGF levels tend to increase, but due to the small test group, further investigations are needed [ 42 ].…”
Section: Possible Utilities Of Vegf Family Members In Colorectal Cancermentioning
confidence: 99%
“…By means of their role in transmitting signals between cells, microparticles constitute a connection between coagulation processes and local inflammation [ 28 , 29 ]. They also play a role in the progression of cancer [ 36 ]. MPs are able to modify the activity of certain medicines due to their sequestration [ 29 ].…”
Section: Introductionmentioning
confidence: 99%